Microbial safety and stability of avocado–turmeric oil-based herbal milk as a basis for food safety education in public health promotion - Winarni, Sri; Mustafa, Annasari; Kurniawati, Atik (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Herbal milk formulated with avocado oil and turmeric is a functional beverage with potential health benefits, but its microbiological safety requires evaluation to determine appropriate storage conditions. Objective: This study aimed to analyze the effects of storage temperature and duration on total bacterial count (Total Plate Count/TPC) as well as the presence of Escherichia coli, coliforms, Staphylococcus aureus, and Enterobacteriaceae. Methods: A laboratory experimental design using a factorial Completely Randomized Design (CRD) was applied, involving two factors: storage temperature (4°C, 25°C, and 40°C) and storage duration (0, 3, and 7 days). Results: The results showed that storage at 4°C effectively affected microbial growth, indicated by a decrease in TPC from 5.51 log CFU/mL to 2.57 log CFU/mL on day 7. In contrast, storage at room temperature (25°C) and elevated temperature (40°C) led to increased microbial activity during the first three days. Conclusion: Overall, storage at 4°C is recommended as the safest condition, with a maximum storage duration of seven days to maintain the microbiological safety and stability of the avocado–turmeric herbal milk.